The protective role of phloretin against dextran sulfate sodium-induced ulcerative colitis in mice. Issue 1 (3rd January 2019) - Zhang, Zecai; Li, Shan; Cao, Hongyang; Shen, Peng; Liu, Jiuxi; Fu, Yunhe; Cao, Yongguo; Zhang, Naisheng
Abstract : Oral administration of phloretin, mainly found in apples and strawberries, ameliorates ulcerative colitis in mice. Abstract : Phloretin, a dihydrogen chalcone flavonoid, is mainly isolated from apples and strawberries. Phloretin has been proven to have many biological activities such as anti-inflammatory and anti-oxidative. Herein, we investigated the protective efficacy and potential mechanism of phloretin in dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) in mice. The results showed that phloretin resulted in a reduced DSS-induced disease activity index (DAI), colon length shortening and colonic pathological damage. The levels of pro-inflammatory cytokines in the colon were also decreased by the administration of phloretin. Exploration of the potential mechanism demonstrated that phloretin suppressed the inflammatory response by regulating the nuclear factor-κB (NF-κB), toll-like receptor 4 (TLR4) and peroxisome proliferator-activated receptor γ (PPARγ) pathways. Phloretin also inhibited the DSS-induced (NOD)-like receptor family and pyrin domain containing 3 (NLRP3) inflammasome activations. Further studies found that phloretin reduced key markers of oxidative stress as well as regulated the expression of zonula occludens-1 (ZO-1) and occludin. Interestingly, the concentration of serum lipopolysaccharide (LPS) was significantly decreased. Escherichia coli ( E. coli ) and Lactobacillus levels were also re-balanced after phloretin treatment. These results indicate that phloretin might be a new dietary strategy for the treatment of UC.